Utilization of non-steroidal anti inflammatory drugs at Klang primary healthcare clinics / Khairani Azian Khairudin - Khairudin, Khairani Azian (2015)
Non-steroidal Anti Inflammatory Drugs (NSAIDs) are among the most frequently prescribed medications worldwide especially in the developed countries. NSAIDs are a common cause of reported adverse drug side-effects and their safety profiles always become a concern. Despite its therapeutic effects, NSAIDs is associated with side effects involving the upper gastro-intestinal tract (GIT), cardiovascular system and renal function. This is a retrospective drug utilization study of NSAIDs available at Klang Health District primary healthcare government clinics. Patient's data who were NSAIDs user were extracted from electronic system namely e-CMS system. The Defined Daily Dose (DDD) and anatomical therapeutic chemical (ATC) were used in the analysis and comparison of data. The objective of the study is to describe the utilization pattern of non-steroidal anti-inflammatory drugs (NSAIDs) at Klang Health District primary healthcare clinics. The specific objectives for this study are to assess the pattern of NSAIDs prescribed, to estimate Define Daily Dose (DDD) for each NSAIDs prescribed, to determine relation in pattern of NSAIDs usage with patient's characteristics and to identify potential NSAIDs prescription related problem. A total of 852 records were retrieved from 3 respective clinics namely Klinik Kesihatan Anika, Bukit Kuda and Pandamaran with the mean age of 45.5 years old (SD 1.63). Based on their DDD's, the most prescribed NSAIDs were Diclofenac (1.5725), Mefenamic Acid (1.4108), Ibuprofen (0.0166) and Meloxicam (0.0016).